Did “The Gnostic Heresy” Influence Valentinus? An Investigation of Irenaeus, Against Heresies 1.11.1 and 1.29 - Litwa, M. David (Vigiliae Christianae, 2024)
This article argues (1) that there is insufficient evidence to conclude that a or the “gnostic heresy” (Irenaeus, Against Heresies 1.11.1) referred to a specific social group whose theology is witnessed in Against Heresies 1.29 and (2) that the aeonology in this passage influenced Valentinus. There is no evidence that the aeonology in Against Heresies 1.29 existed prior to 160 CE, the approximate date of Valentinus’s demise; thus this material could not have shaped Valentinus’s theology. Instead of thinking with Irenaeus in terms of unidirectional influence (Irenaeus’s constructed “gnostic heresy” inspiring Valentinus/Valentinians), future theories ought to account for multiple directions of influence and entanglement between various early Christian theologians in the late second century CE.